Evaluation of Quebracho Red Wood (Schinopsis lorentzii) Polyphenolic Vegetable Extract for the Reduction of Coccidiosis in Broiler Chicks - Cejas, Emanuel; Pinto, Silvina; Prosdocimo, Florencia; Batalle, Mariano; Barrios, Hebe; Tellez , Guillermo; Franceschi, Mauricio De (International Journal of Poultry Science, 2011)
The effects of a commercially available Polyphenolic Vegetable Extract (PVE) from Schinopsis lorentzii (Bioquina®) for the reduction of coccidiosis in broiler chicks was evaluated. Day-of-hatch male broiler chicks were obtained from a local hatchery and randomly assigned to three experimental groups consisting of 8 chickens per group with four replicates per treatment: Group 1, PVE 10% - challenged; Group 2, untreated - challenged and Group 3, -untreated, non-challenged. Heated brooder batteries were used for housing and chicks were allowed ad libitum access to unmedicated broiler rations and water for the duration of the experiment. On day 21 post-hatch, all birds in groups 1 and 2 were challenged by oral gavage with 3 mL of a mixed suspension of freshly sporulated oocysts of Eimeria tenella (50,000 oocyst/mL), E. maxima (50,000 oocyst/mL) and E. avervulina (50,000 oocyst/mL). Group 3 was sham inoculated with 3 mL of PBS. Body weight gain was obtained seven days after coccidia challenge. Oocyst sheeding was performed at 5, 7 and 10 days PI. Intestinal macroscopic lesions and histological morphometric analysis was performed 7 days PI. No significant differences were observed in terms of total mortality or lesion scores. Supplementation of PVE significantly increased body weight gain, crypt:villi ratio and decreased oocyst excretion (p